APC Promoter Methylation in Gastrointestinal Cancer - Zhu, Lila; Li, Xinyu; Yuan, Ying; Dong, Caixia; Yang, Mengyuan (Frontiers in Oncology, 2021)
The adenomatous polyposis coli (APC) gene, known as tumor suppressor gene, has the two promoters 1A and 1B. Researches on APC have usually focused on its loss-of-function variants causing familial adenomatous polyposis. Hypermethylation, however, which is one of the key epigenetic alterations of the APC CpG sequence, is also associated with carcinogenesis in various cancers. Accumulating studies have successively explored the role of APC hypermethylation in gastrointestinal (GI) tumors, such as in esophageal, colorectal, gastric, pancreatic, and hepatic cancer. In sporadic colorectal cancer, the hypermethylation of CpG island in APC is even considered as one of the primary causative factors. In this review, we systematically summarized the distribution of APC gene methylation in various GI tumors, and attempted to provide an improved general understanding of DNA methylation in GI tumors. In addition, we included a robust overview of demethylating agents available for both basic and clinical researches. Finally, we elaborated our findings and perspectives on the overall situation of APC gene methylation in GI tumors, aiming to explore the potential research directions and clinical values.